COVID-19 pandemic in India: A Comparison of pandemic pattern in Selected States - Rath, Rama Shankar; Dixit, Anand Mohan; Koparkar, Anil Ramesh; Kharya, Pradip; Joshi, Hari Shanker (Nepal Journal of Epidemiology, 2020)
The COVID-19 pandemic currently expanded its roots to the 206 countries in the world. The morbidity and mortality are not only threat to humans but also its impact on economy is indirectly affecting us. The current review was done to find trend in various states of India. Data was collected from Ministry of Health and Family Welfare and descriptive analysis of the distribution of COVID-19 cases in different states of India. First case of COVID-19 was diagnosed in southern most state Kerala and after that it has spread to all other states but situations are more worsen in states with high international migration. Maharashtra is now the most affected state followed by Delhi. Among epidemic curve of all these states, Maharashtra has rapidly growing epidemic curve with highest slope, whereas Kerala has the lowest. When we compared the day wise cumulative case fatality rate, it was found that the case fatality rate of the states like Maharashtra, Madhya Pradesh & Rajasthan showed decrease in the case fatality rate over the period. Population density is also one of the key determinants of social interaction and thus the spread of disease specifically in communicable diseases. Government of India had taken many strong initiatives e.g. 40 days nation-wide lockdown, thermal screening at airport, announcement of relief packages for poor and quarantine of outsiders but still there are many missed opportunities like, early stoppage of international traffic, compulsory quarantine for all international travellers, better contact tracing, strong law and order and better preparedness plan.